2021
DOI: 10.3847/2041-8213/ac0437
|View full text |Cite
|
Sign up to set email alerts
|

The Enigmatic Brown Dwarf WISEA J153429.75-104303.3 (a.k.a. “The Accident”)

Abstract: Continued follow-up of WISEA J153429.75−104303.3, announced in Meisner et al., has proven it to have an unusual set of properties. New imaging data from Keck/MOSFIRE and HST/WFC3 shows that this object is one of the few faint proper motion sources known with J − ch2 >8 mag, indicating a very cold temperature consistent with the latest known Y dwarfs. Despite this, it has W1−W2 and ch1−ch2 colors ∼1.6 mag bluer than a typical Y dwarf. A new trigonometric parallax measurement from a combination of WISE, Spitzer,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…No currently available theoretical atmosphere model reproduces the optical-to-infrared spectrum of WISE1810. Finally, we conclude that the density of metal-poor brown dwarfs in the solar neighbourhood might be higher than expected due to the revised distance of WISE1810 and the recent Y-type 'accident' reported by Kirkpatrick et al (2021b).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…No currently available theoretical atmosphere model reproduces the optical-to-infrared spectrum of WISE1810. Finally, we conclude that the density of metal-poor brown dwarfs in the solar neighbourhood might be higher than expected due to the revised distance of WISE1810 and the recent Y-type 'accident' reported by Kirkpatrick et al (2021b).…”
Section: Discussionmentioning
confidence: 57%
“…WISE1810 has the same H − K and H − W2 colours and bolometric luminosity as T8-T9 solar-metallicity dwarfs. WISE1810 is bluer in W1 − W2, pointing towards a low metallicity as discussed in Schneider et al (2020) and Kirkpatrick et al (2021b) and it is redder in the J − H and J − W1 colours. In addition to these peculiarities, we found that it is bluer in the z − J colour, which may also be attributed to a low metallicity.…”
Section: Bolometric Luminositymentioning
confidence: 59%
See 2 more Smart Citations
“…Five objects were identified as members of this population: CWISEP J015613.24+325526.6 (CWISEP 0156 +3255 for short), CWISEP J050521.29−591311.7 (CWISEP 0505−5913 for short), CWISEP J070055.19+783834.0 (CWISEP 0700+7838 for short), CWISEP J090536.35 +740009.1 (CWISEP 0905+7400 for short), and WISEA J153429.75−104303.3 (WISEA 1534−1043 for short). WISEA 1534−1043 was highlighted as especially unusual in a later paper by Kirkpatrick et al (2021b), which explored a variety of possible scenarios for explaining this object, concluding that it is likely metal-poor, and perhaps the first Y-type subdwarf. This work provides new near-infrared photometry for the three sources with the reddest J − [4.5] color among these five candidates, suggesting they may be the colder sources: CWISEP 0156+3255, CWISEP 0505−5913, and WISEA 1534−1043.…”
Section: Target Selection For New Near-infrared Photometrymentioning
confidence: 98%